2016
DOI: 10.17306/j.npt.2016.4.53
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of true aloe (Aloe vera) extract in model systems

Abstract: SummaryBackground. Aloe contains numerous bioactive compounds which are attributed to have health advantages. Widely used in the cosmetic and pharmaceutical industries, also found its application in the food industry. The antioxidant compounds in aloe may increase the stability and nutritional value of food. The aim of the paper was to evaluate the results of the antioxidant properties of aqueous extract of aloe in model systems. Material and methods. Analyses were conducted on true aloe (Aloe vera L.). Extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…7b, the optical band gap was obtained by extrapolating a straight line to the Tauc plot. The optical band gap of ZnO nanoparticles was estimated about 3.47 eV, which is in good agreement with the published literature (Ibrahim et al 2017;Hęś et al 2016;Kasaai 2013;Zhu et al 2014). At room temperature, ZnO shows a band gap of 3.37 eV at an absorption peak of 375 nm.…”
Section: Uv-vis Analysis Of Nanoparticlessupporting
confidence: 90%
See 1 more Smart Citation
“…7b, the optical band gap was obtained by extrapolating a straight line to the Tauc plot. The optical band gap of ZnO nanoparticles was estimated about 3.47 eV, which is in good agreement with the published literature (Ibrahim et al 2017;Hęś et al 2016;Kasaai 2013;Zhu et al 2014). At room temperature, ZnO shows a band gap of 3.37 eV at an absorption peak of 375 nm.…”
Section: Uv-vis Analysis Of Nanoparticlessupporting
confidence: 90%
“…Aloe Vera extract has greater antibacterial properties against bacteria (Ibrahim et al 2017). Aloe vera contains polyphonls, anthranoids and mineral components (chromium, calcium, iron, manganese, phosphorus, potassium and zinc) as well as vitamins (C, E, B1, B2, B3, B6, B12 and folic acid) (Hęś et al 2016;Kasaai 2013). Therefore, to impart excellent antibacterial properties and laundering durability, cotton fabric can be treated with DBD plasma and Aloe vera gel and coated with ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Sample 1 showed I % = 5.14 μmol Trolox mL −1 , sample 2 showed I % = 2.62 μmol Trolox mL −1 , sample 3 showed I % = 1.41 μmol Trolox mL −1 , sample 4 showed I % = 2.13 μmol Trolox mL −1 , and sample 5 showed I % = 0.73 μmol Trolox mL −1 . According to Hęś et al ., 31 aqueous A. vera leaf extracts antioxidant activity using the ABTS · + assay found I % varied from 0.58 to 0.87 mg Trolox mL −1 , indicating that the A. vera plant has low antioxidant capacity. As also mentioned previously, for the DPPH · assay the antioxidant capacity of A. vera is relatively low compared with plants such as oregano and sage, at I % = 1.73 μmol Trolox mL −1 and 0.62 μmol Trolox mL −1 respectively; 32 in contrast, goji berry, which is known for its high antioxidant activity, was found to reach I % = 8.35 μmol Trolox mL −1 33 …”
Section: Resultsmentioning
confidence: 99%
“…Sample 1 showed I% = 9.21 μmol Trolox mL −1 , sample 2 showed I% = 8.91 μmol Trolox mL −1 , sample 3 showed I % = 8.15 μmol Trolox mL −1 , sample 4 showed I% = 2.61 μmol Trolox mL −1 , and sample 5 showed I% = 1.64 μmol Trolox mL −1 . Hęś et al, 31 by applying the same assay, showed that A. vera leaf aqueous extracts had I% from 4.32 to 8.87 mg Trolox mL −1 , with the result that A. vera aqueous extract presents relatively low antioxidant capacity. Compared with other plants' antioxidant capacities, such as oregano and sage, which have I% = 1.62 μmol Trolox mL −1 and 0.42 μmol Trolox mL −1 respectively, 32 when estimated by the DPPH • assay, A. vera shows a relative lower antioxidant capacity; this compares with goji berry, which is known for its high antioxidant activity, for which I% = 10.62 μmol Trolox mL −1 .…”
Section: Dpph • Assaymentioning
confidence: 93%
“…A. vera contains great numbers of antioxidant compounds which may help in increasing nutritional value and stability of food. It has been reported that the use of different model system showed different antioxidant properties of the extract of A. vera (Hęś et al, 2016). The cytotoxic and antioxidant activity were reported by López et al (2017).…”
Section: Antioxidant Activitymentioning
confidence: 93%